2014
DOI: 10.1021/jz501163r
|View full text |Cite
|
Sign up to set email alerts
|

Surface Photovoltage Spectroscopy Study of Organo-Lead Perovskite Solar Cells

Abstract: The field of organo-lead perovskite absorbers for solar cells is developing rapidly, with open-circuit voltage of reported devices already approaching the maximal theoretical voltage. Obtaining such high voltages on spun-cast or evaporated thin films is intriguing and calls for detailed investigation of the source of photovoltage in those devices. We present here a study of the roles of the selective contacts to methylammonium lead iodide chloride (MAPbI3-xClx) using surface photovoltage spectroscopy. By depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 38 publications
6
73
0
Order By: Relevance
“…It has been suggested that the V oc in the cell is primarily generated by the electron extraction layer/MAPI contact. 12 If so, then the shift in the CI peak voltage in figure 4b indicates changes in dipole/charge density at the mpTiO 2 / MAPI and/or sTiO 2 /MAPI interfaces. The capacitance in figure 3c, 2 µF/cm 2 , is similar to the capacitance measured for planar TiO 2 films facing electrolyte.…”
Section: Current Interrupt Voltage and Band Offsetsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested that the V oc in the cell is primarily generated by the electron extraction layer/MAPI contact. 12 If so, then the shift in the CI peak voltage in figure 4b indicates changes in dipole/charge density at the mpTiO 2 / MAPI and/or sTiO 2 /MAPI interfaces. The capacitance in figure 3c, 2 µF/cm 2 , is similar to the capacitance measured for planar TiO 2 films facing electrolyte.…”
Section: Current Interrupt Voltage and Band Offsetsmentioning
confidence: 98%
“…There is also debate about how to correctly measure the recombination and transport times, the charge density, and even the correct measurement of efficiency. [5][6][7][8][9][10][11][12][13][14][15][16][17] The debate about characterization centers on the interpretation of various time constants that can be measured by optical and electrical means. These time constants range from <1 µs to >100 µs.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the enormous potential for characterization of Kelvin probe has been employed to investigate the role of selective contacts in perovskite solar cells, exploring the surface of the samples. 18 Here, KPFM has been employed for the characterization of the cross-sectional potential distribution in complete devices. Fig.…”
Section: à3mentioning
confidence: 99%
“…5b. As is seen, through 370 to 650 nm, the SPV signal of P3HT NWs:CdSe NTs hybrid device produces an obviously enlarged SPV signals compared to that of the P3HT:CdSe NTs reference, indicative of an increased number of charges that can transport to the hybrid film surface after exciton dissociation [34, 35]. …”
Section: Resultsmentioning
confidence: 99%